PERBANDINGAN FORGIVENESS PADA WANITA KORBAN KDRT DITINJAU DARI KEHADIRAN ANAK - Ariyani, Mira; Qonita, Maryam (Journal of Research and Measurement in Psychology: JPPP, 2018)
The purpose of this study was to find out the comparison in forgiveness of women victims of domestic violence in terms of the presence of children. The research used quantitative method wtith t-test technique to compare the means of two groups sample. The sample in this study for women with children is 30 respondents. And The sample in this study for women without children is 30 respondents. The sampling techniques used in this research is non probablity sampling test. Data obtained using The Transgression-Related Interpersonal Motivations Inventory-18 (TRIM-18) designed by McCoullough and adopted by researcher. Based on analysis data using independent t-test technique, its known that t t = -,0444 < 2.002; p =0,639 > 0,05. Based on the results, this means that there is no significant difference of forgiveness in women victims of domestic violence reviewed from children presence.